Principal Leadership Style at Vocational High School (SMK) PGRI Selaawi Garut - Deti Rostini; Tentri Septiyani; Syatiri Ahmad; Dudi Suprihadi; Nur Ainiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This study aims to describe the leadership style of school principals at the PGRI Selaawi Vocational High School (SMK), Garut Regency. This research uses a descriptive research design that uses research informants, namely deputy principals as key informants and principals, educators and education staff as supporting informants. Data collection techniques using interviews, observation and documentation. Data analysis techniques use interactive models, namely data reduction, data presentation, and drawing conclusions. Data validity was carried out using source and method triangulation techniques. The results of the study show that (1) the leadership style played by the principal with a leadership type that tends to be democratic. (2) The implementation of the principal's leadership includes: a planning process using good, orderly and open management. The organizing process is carried out with a good leadership style with the division of tasks between educators and education staff. The process carried out with a patterned leadership style strengthens cooperative relationships by always providing direction, coaching, formally and non-formally, both at meetings or personally. Supervision is carried out to give confidence to subordinates so that they do not continuously carry out supervision by going around the class, supervising the performance of educators and education staff. (3) Decision making is carried out by the principal with a leadership style by way of deliberation and discussion and involving educators, education staff and all existing stakeholders.